RITUAL JERE DALAM SISTEM RELIGI DI KELURAHAN OME KECAMATAN TIDORE UTARA KOTA TIDORE PROPINSI MALUKU UTARA - Sofyan, Firdaus; Matheosz, Jenny Nelly; Mawara, Jetty E. T. (Universitas Sam Ratulangi, 2018)
Jereis the building stones of the composition that is believed to have supernatural powers by residents of North Maluku. Ritual Jere is one of the cultural relics of the megalithic heritage (large stone) is still practiced in the life of the community, North Maluku particularly Tidore. In scientific or archaeological Antiquities subsume Jere building site as the phallus. Commemorative site in General is indeed used as one of the media in religious practice for the community supporting the culture. This study uses qualitative methods, so that research can generate descriptive data that is in the form of words, the source data is written and the photos. The results of the data in the form of the words, able to explain existing problems.Jere ritual or sacred tomb is a pilgrimage to the traditions of the societies that have the dual dimension of Ome, namely as a sacred religious ritual full of meaning and as a cultural tradition. The ritual was entirely related to jere tomb of the people who spread the religion of Islam which were sacred, because he has these advantages that cannot be explained with logic. Goals and purpose of ritual execution because of a strong desire to tawasul (convey greetings) to such person as a mediator who is believed to be able to forward your prayer requests to God, due to the proximity of him with God.Keywords : Jere, religious, ritual